Essays on the role of contagion and integration in international issues of South America - Reis, Felipe Alves (2017)
The emerging economies of South America commonly attract the attention of researchers, even if for punctually different reasons among the economies in question. These economies include the strong Chilean financial market, the consolidated domestic demand of the Brazilian population, the Argentine anti-democratic convergence, the process of internal pacification in Colombia, or even the high growth rates of the Peruvian economy. In addition to this, we highlight the results of Matos, Siqueira & Trompieri (2014) that show the existence of a high level of integration and the financial contagion among the indices of Brazil, Argentina, Colombia, Chile, Peru and Venezuela. In light of these evidences, this thesis presents three essays on financial and economic data from Brazil, Argentina, Colombia, Chile and Peru. In the first essay, we analyze the risk market of these economies using the Value at Risck - VaR conditional methodology, in which the critical value that characterizes the VaR is associated to the distribution that presents the best fitting, and we incorporate the effects of the mean and the volatility, both conditional, obtained by the best-specified ARMA-GARCH model, showing that the best fitting conditional models have a smaller number of violations. The second essay presents the analysis of international reserves, conceptually following the notions of the Buffer Stock methodology, but considering the significant cross-effects of conditional volatilities, their respective spreads and intra-block importation. The results point to both a significant improvement in the explanatory power of the model and that the Brazilian reserves are the least affected by South American economies. In the last essay, we analyze some diversified portfolio options available to a Brazilian investor, who faces a scenario with no opportunities in the financial market, with the purpose of measuring gains with diversification of the position acquired in the South American market indices vis-à-vis the domestic portfolio. The results show the possibility that simple and non-dynamic portfolio composition strategies, composed only of indexes of the markets of the neighboring countries of Brazil, translate into very satisfactory results in terms of expected gain and risk.